Five recommendations to accelerate sustainable solutions in cement and concrete through partnership - Joseph Mwiti Marangu; Alastair T M Marsh; Daman K Panesar; Nonkululeko W Radebe; Alicia Regodon Puyalto; Wolfram Schmidt; Luca Valentini (RILEM Technical Letters, 2023)
Though the technical knowledge to make cement and concrete more sustainable already exists, implementation of solutions lags behind the rate needed to mitigate climate change and meet the targets set by the Sustainable Development Goals. Whilst most of the focus around the built environment is on embodied carbon, we stress an important but neglected dimension: partnership (SDG17). Effective partnerships can be powerful enablers to accelerate sustainable solutions in cement and concrete, and let such solutions transfer from academia to the market. This can be achieved through knowledge generation, solution implementation, and policy development, among other routes. In this article, we share five recommendations for how partnerships can address neglected research questions and practical needs: 1) reform Science, Technology, Engineering and Mathematics (STEM) education to train “circular citizens”; 2) map out routes by which cementitious materials can contribute to a “localization” agenda; 3) generate open-access maps for the geographical distribution of primary and secondary raw materials; 4) predict the long-term environmental performance of different solutions for low-CO2 cements in different geographical areas; 5) overhaul standards to be technically and regionally fit for purpose. These approaches have the potential to make a unique and substantial contribution towards achieving collective sustainability goals.